Curculigo orchioides Gaertn.: An Overview of Its Effects on Human Health - Kushalan, Sharanya; Khyahrii, Aloysius S.; Kini, Sudarshan; Hegde, Smitha (Journal of Health and Allied Sciences NU, 2022)
Curculigo orchioides, commonly called “Kali Musli,” is an endangered medicinal plant commonly found in Asian countries such as India, Japan, China, and Nepal. The plant holds a significant position in Ayurvedic and the Chinese traditional medicine system; it is documented as an aphrodisiac herb. The plant is also reported to be used in the treatment for asthma and jaundice. The botany, traditional uses, phytochemistry, and pharmacological activities to evaluate the plant's importance and relevant information are reviewed and summarized. We discern that a total of 61 phytochemicals are identified and reported in C. orchioides. These belong to the various phytochemical group of glycosides, lignans, polysaccharides, alkaloids, saponins, triterpenes, and aliphatic compounds. The most explored bioactive compound is a phenolic glycoside, curculigoside, isolated from the plant's rhizome. In vitro and in vivo research is conducted globally to provide primary and robust evidence to support this herbal medicine's traditional uses. A large lacuna regarding the mechanisms involved in the biological activity of the plant is evident. There is a need to conduct in-depth studies to understand the relationship between traditional and modern pharmacological uses of C. orchioides.
Keywords: Curculigo orchioides; phytochemistry; bioactivity; medicinal herb